Pursuing pademelon provenance: a pilot study using portable XRF to trace field-collection of museum mammal specimens - Celia Cramer; Elizabeth A. Carter; Brad Swarbrick; Jude Philp; Peter A. Lay (Heritage Science, 2023)
Abstract Internationally, the value and usefulness of museum zoological specimens are compromised when supporting contextual data are lost or disconnected from the specimen. In this pilot study, twelve Macropodidae Thylogale (pademelon) skins with known provenance from the Australian Museum (Sydney) were analysed using portable X-ray fluorescence spectroscopy and principal component analysis. Elemental composition of preservative residues was assessed to establish if common patterns existed and could be associated with particular field collectors. Specimens were differentiated, and the field collector deduced, based on elemental analysis of preservative residues on skins. Each of the nineteenth century field collectors, in this study, were found to have applied the same or similar preservatives to zoological specimens over a number of years, which showed a consistent pattern of practice. Additionally, the specimens obtained by each of the field collectors could be distinguished from one another based on the preservative residues. These discoveries provide exciting prospects for the use of X-ray fluorescence spectroscopy to couple museum specimens with unknown contextual data via their field collector and associated archival evidence, and hence, enable a considerable enhancement of their value as museum and research objects.